An IP transport and routing architecture for next-generation satellite networks. - Yegenoglu, F. (IEEE Network : the magazine of global information exchange)
Over the past several years, a number of new satellite systems have been proposed to provide high-speed Internet and multimedia services to businesses and home users. These proposals have been driven by the desire of network operators to reach end users that do not have cost effective access to other alternatives such as fiber, DSL, and cable, and by the availability of new spectrum (Ka-band) for use by new satellite services. The proposed systems generally employ multiple high-power spot beams, an onboard fast packet switch, and a demand-assigned multiple access scheme to provision IP-based services. In this article we concentrate on a geosynchronous satellite system where packet transport and switching within the satellite system are based on ATM. We describe an IP/ATM interworking and IP routing architecture that is driven by three main requirements: (1) the ability to support ATM SVCs between hundreds of thousands of satellite terminals by a single ATM switch located onboard; (2) a scalable IP routing architecture that does not result in large volumes of routing traffic to be transported over the satellite; and (3) the ability to segment the satellite terminals for routing and administrative control by ISPs and enterprise networks